2018
DOI: 10.1080/08897077.2018.1439800
|View full text |Cite
|
Sign up to set email alerts
|

An Opioid Overdose Curriculum for Medical Residents: Impact on Naloxone Prescribing, Knowledge, and Attitudes

Abstract: A brief curricular intervention improved resident knowledge and attitudes regarding intranasal naloxone for opioid overdose reversal and significantly increased prescribing rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
0
15
1
Order By: Relevance
“…[54][55][56] Dedicated training regarding SUD screening, diagnosis, and treatment during residencies could better prepare PCPs to care for PWID. [57][58][59] Hospital campaigns to train front-line staff and reduce providers' stigmatizing language in favor of person-first language may also help reduce the stigma experienced by PWID. 60,61 Primary care for PWID is important because it provides a potential "one-stop shop" for addressing complex healthcare needs.…”
Section: Discussionmentioning
confidence: 99%
“…[54][55][56] Dedicated training regarding SUD screening, diagnosis, and treatment during residencies could better prepare PCPs to care for PWID. [57][58][59] Hospital campaigns to train front-line staff and reduce providers' stigmatizing language in favor of person-first language may also help reduce the stigma experienced by PWID. 60,61 Primary care for PWID is important because it provides a potential "one-stop shop" for addressing complex healthcare needs.…”
Section: Discussionmentioning
confidence: 99%
“…Our pilot of a naloxone didactic and skills session for primary care learners demonstrated substantial improvements in the domains of knowledge, self-efficacy, and attitudes. Prior studies have reported several barriers to practicing physicians incorporating naloxone into care of patients with substance use disorders including knowledge gaps in use and proper administration with those who have never received naloxone training 28. Given that the ACGME currently does not specifically require any education or curricular activities regarding opioid use disorder treatment, our training model provides a unique opportunity to address a critical gap in knowledge and skills for primary care providers who will encounter this epidemic in many dimensions in practice.…”
Section: Discussionmentioning
confidence: 99%
“…The pilot results of our training model demonstrated improvement in comfort levels administering four different methods of naloxone. Exposure to training, as suggested by others, in addition to personal experiences with patients and/or family members can impact necessary changes in behaviors and attitudes toward providing access to naloxone for patients who would benefit most 28,29…”
Section: Discussionmentioning
confidence: 99%
“…A search of MedEdPORTAL using the keyword naloxone identified three unique publications: One includes naloxone training within a larger multiday substance use disorder training session for students, 11 another discusses an adverse event for pulmonary edema after naloxone administration, 12 and the third addresses indications for naloxone for inpatient opioid reversal. 13 While there is literature on the importance of naloxone training for medical trainees, 14 our curriculum is unique in that it is a standalone brief workshop whose primary focus is on naloxone education for health care providers. Even though the initial curriculum was developed for residents and fellows, it is generalizable to the medical community at large.…”
Section: Introductionmentioning
confidence: 99%